2019
DOI: 10.1021/acsanm.9b01913
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Fluoroquinolone-Based Pollutants and Bacterial Inactivation by Visible-Light-Active Aluminum-Doped TiO2 Nanoflakes

Abstract: The development of a visible-light-active photocatalyst for the removal of organic contaminants from water is of primary importance. In this work, we have developed a one-pot synthesis method for visible-light-active aluminum-doped titania (TiO2) with highly efficient sorption degradation of the fluoroquinolone-based pharmaceutical pollutant norfloxacin in aqueous solution. Here, we reduced the effective band gap of TiO2 by in situ doping of aluminum (1 mol %), which significantly improves the porosity, result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…The peak with the binding energy of 530.01 eV corresponds to the lattice O originating from the material. The other peak situated on higher binding energy at 532.50 eV results from the adsorbed O species from the environment shown in Figure 2F 33 . For Ag, signature peaks at 368.43 and 474.38 eV correspond to Ag 3d 5/2 and Ag 3d 3/2 spin‐orbital state.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The peak with the binding energy of 530.01 eV corresponds to the lattice O originating from the material. The other peak situated on higher binding energy at 532.50 eV results from the adsorbed O species from the environment shown in Figure 2F 33 . For Ag, signature peaks at 368.43 and 474.38 eV correspond to Ag 3d 5/2 and Ag 3d 3/2 spin‐orbital state.…”
Section: Resultsmentioning
confidence: 95%
“…The other peak situated on higher binding energy at 532.50 eV results from the adsorbed O species from the environment shown in Figure 2F. 33 For Ag, signature peaks at 368.43 and 474.38 eV correspond to Ag 3d 5/2 and Ag 3d 3/2 spin-orbital state. These peaks indicate the presence of a metallic form of Ag, as shown in Figure 2G.…”
Section: Resultsmentioning
confidence: 96%
“…Photo-generated electrons and holes that can potentially help to produce active oxygen and kill bacteria. [8][9][10] In the absence of light, it was found that TiO 2 can alter the bacterial cell wall morphology and permeability, thereby regulate the osmotic balance of bacteria. [6,[11][12][13] Among the carbon-based nanomaterial with antimicrobial properties, graphene oxide (GO) has received extensive attention due to its unique physical and chemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…So far, antibacterial properties of TiO 2 can be attributed to its excellent photoactivation properties. Photo‐generated electrons and holes that can potentially help to produce active oxygen and kill bacteria [8–10] . In the absence of light, it was found that TiO 2 can alter the bacterial cell wall morphology and permeability, thereby regulate the osmotic balance of bacteria [6,11–13] …”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of photoelectrochemical splitting of water on TiO 2 in 1972, [ 18 ] after decades of research, researchers have been able to prepare a variety of TiO 2 with different morphologies, including nanospheres, [ 19–21 ] nanowires, [ 22 ] nanotubes, [ 23 ] nanosheets [ 24 ] and nanofibers, [ 25 ] and so on. The nanoscale spherical TiO 2 (Degussa P25) is the only commercial mass‐produced morphology with good degradation properties.…”
Section: Introductionmentioning
confidence: 99%